2005
DOI: 10.1194/jlr.m400505-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Acute inhibition of hepatic β-oxidation in APOE*3Leiden mice does not affect hepatic VLDL secretion or insulin sensitivity

Abstract: Hepatic VLDL and glucose production is enhanced in type 2 diabetes and associated with hepatic steatosis. Whether the derangements in hepatic metabolism are attributable to steatosis or to the increased availability of FA metabolites is not known. We used methyl palmoxirate (MP), an inhibitor of carnitine palmitoyl transferase I, to acutely inhibit hepatic FA oxidation and investigated whether the FAs were rerouted into VLDL secretion and whether this would affect hepatic glucose production. After an overnight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
2
7
0
Order By: Relevance
“…Even if increased hepatic triglyceride content is commonly thought to be associated with reduced insulin sensitivity (31), our evidence are in agreement with the results of studies in which liver steatosis induced by acute treatment with TDGA in C57BL/6J mice, or with methylpalmoxirate in hyperlipidemic APO3*Leiden mice, does not induce liver insulin resistance (32,33). In addition, Buettner et al (34) perfusing ex vivo livers from high-fat-fed Wistar rats showed that increased intracellular lipids per se do not induce defects in insulin action, reporting that fasting-induced hepatic steatosis is not associated with an impairment of liver insulin sensitivity in healthy rodents (35), suggesting alternative extrahepatic regulators of liver insulin sensitivity other than triglycerides.…”
Section: Discussionsupporting
confidence: 91%
“…Even if increased hepatic triglyceride content is commonly thought to be associated with reduced insulin sensitivity (31), our evidence are in agreement with the results of studies in which liver steatosis induced by acute treatment with TDGA in C57BL/6J mice, or with methylpalmoxirate in hyperlipidemic APO3*Leiden mice, does not induce liver insulin resistance (32,33). In addition, Buettner et al (34) perfusing ex vivo livers from high-fat-fed Wistar rats showed that increased intracellular lipids per se do not induce defects in insulin action, reporting that fasting-induced hepatic steatosis is not associated with an impairment of liver insulin sensitivity in healthy rodents (35), suggesting alternative extrahepatic regulators of liver insulin sensitivity other than triglycerides.…”
Section: Discussionsupporting
confidence: 91%
“…Apparently, plasma FA levels and FA availability to the liver per se do not determine hepatic VLDL-TG production. In accord with this notion, we have previously shown that acute redirection of hepatic FA flux from ␤-oxidation to storage does not affect hepatic VLDL-TG production (8). We suggest that, under the conditions of our experiment, insulin exerts direct effects on hepatic VLDL-TG production that are apparently of greater importance than the indirect effects via suppression of FA release from adipose tissue or FA availability in general, at least under the conditions of our experiments.…”
Section: Discussionsupporting
confidence: 86%
“…First, it has been generally assumed that, via increased FA ␤-oxidation, fenofibrate reduces the amount of FA available for VLDL-TG output (5). However, we previously showed that specific inhibition of FA ␤-oxidation using methyl palmoxirate does not affect VLDL-TG production despite increasing hepatic TG content (45). Moreover, this simplified assumption does not take into account that fenofibrate in fact increases the liverdirected flux of FA/TG.…”
Section: Discussionmentioning
confidence: 88%